Diversity in the medical research ecosystem: a descriptive scientometric analysis of over 49 000 studies and 150 000 authors published in high-impact medical journals between 2007 and 2022 - Leo Anthony Celi; Jonathan Shaffer; Marie-Laure Charpignon; Liam G McCoy; Luis Filipe Nakayama; Jack Gallifant; Urvish Jain; Joao Matos; Pia Gabrielle I Alfonso; Marisa Cobanaj; Amelia Morel Fiske; Alexander J Gates; et al. (BMJ Open)
Objectives Health research that significantly impacts global clinical practice and policy is often published in high-impact factor (IF) medical journals. These outlets play a pivotal role in the worldwide dissemination of novel medical knowledge. However, researchers identifying as women and those affiliated with institutions in low- and middle-income countries (LMICs) have been largely under-represented in high-IF journals across multiple fields of medicine. To evaluate disparities in gender and geographical representation among authors who have published in any of five top general medical journals, we conducted scientometric analyses using a large-scale dataset extracted from the New England Journal of Medicine, Journal of the American Medical Association, The BMJ, The Lancet and Nature Medicine.Methods Author metadata from all articles published in the selected journals between 2007 and 2022 were collected using the DimensionsAI platform. The Genderize.io Application Programming Interface was then used to infer each author’s likely gender based on their extracted first name. The World Bank country classification was used to map countries associated with researcher affiliations to the LMIC or the high-income country (HIC) category. We characterised the overall gender and country income category representation across the five medical journals. In addition, we computed article-level diversity metrics and contrasted their distributions across the journals.Results We studied 151 536 authors across 49 764 articles published in five top medical journals, over a period spanning 15 years. On average, approximately one-third (33.1%) of the authors of a given paper were inferred to be women; this result was consistent across the journals we studied. Further, 86.6% of the teams were exclusively composed of HIC authors; in contrast, only 3.9% were exclusively composed of LMIC authors. The probability of serving as the first or last author was significantly higher if the author was inferred to be a man (18.1% vs 16.8%, p<0.01) or was affiliated with an institution in a HIC (16.9% vs 15.5%, p<0.01). Our primary finding reveals that having a diverse team promotes further diversity, within the same dimension (ie, gender or geography) and across dimensions. Notably, papers with at least one woman among the authors were more likely to also involve at least two LMIC authors (11.7% vs 10.4% in baseline, p<0.001; based on inferred gender); conversely, papers with at least one LMIC author were more likely to also involve at least two women (49.4% vs 37.6%, p<0.001; based on inferred gender).Conclusion We provide a scientometric framework to assess authorship diversity. Our research suggests that the inclusiveness of high-impact medical journals is limited in terms of both gender and geography. We advocate for medical journals to adopt policies and practices that promote greater diversity and collaborative research. In addition, our findings offer a first step towards understanding the composition of teams conducting medical research globally and an opportunity for individual authors to reflect on their own collaborative research practices and possibilities to cultivate more diverse partnerships in their work.